To Be Ok or Not to Be Ok: The Youth Leaders’ Perception on Mental Health - Zulystiawati, Zulystiawati; Ibrahim, Moh. Syahrun (Budapest International Research and Critics University, 2021)
The study was conducted to investigate the perception of youth leaders of University Students Boards about their understanding of mental health and their role to promote mental health awareness campaigns in their context. This study will explore the youth leaders’ perceptions of mental health. This study also covers the youth perspective on their roles as young leaders in their respective departments and faculty-student associations. This study was conducted in four departments of university student associations in from Gorontalo higher education setting. This study used qualitative research with a case study approach with thematic analysis. The research utilized the purposive sampling of student boards. This study employed personal interviews and focus group discussions. The result shows two core themes, as follow: (1) youth leaders’ perception and attitudes towards mental health, and (2) the youth leaders’ engagement in promoting mental health.